Micro Text And Its Cognitive Model - Z. O. Kurbanov (Madrosatuna: Journal of Islamic Elementary School, 2018)
The article examines the problem of cognitive model of the micro text. Here the complex sentence is learned as a micro text in the basis of hierarchical relations of its components. In the process of the analysis of language material local and global structure of the components of the microtext is taken into account, which is important for the definition of its cognitive model. In general, the micro text is defined as a global structure, while its separate components are studied as local structures. It is known, that each syntactic structure has a definite situation beyond the microtext, and its components also have a situation. This is also a basic definition of general and private cognitive model of the microtext.